Seizure and Altered Mental Status After Thoracentesis: Cerebral Air Embolism - Çağrı Safa Buyurgan; Hüseyin Narcı; Cüneyt Ayrık (Eurasian Journal of Emergency Medicine, 2023)

(untitled)
Cerebral air embolism (CAE) is a rare life-threatening condition. It may clinically mimic acute ischemic stroke by decreasing cerebral perfusion pressure and brain tissue oxygenation and may cause impaired consciousness and epileptic seizures. In its etiology; iatrogenic causes such as central venous catheterization, endoscopy, sclerotherapy, major surgeries, and invasive lung interventions are mostly seen. The most useful imaging method for diagnosis is cranial computed tomography (CT). In this presentation, we present the case of a 63-year-old male patient admitted to the emergency department (ED) with complaints of mental status changes and seizures and weakness in the left upper and lower extremities on physical examination. The patient had a history of thoracentesis performed three days ago and was discharged. Brain CT of the patient showed signs of newly developing CAE, and diffusion magnetic resonance imaging showed findings consistent with right middle cerebral artery infarction in his second admission. We thought that the symptoms of the patient, who had no history of additional intervention, were due to CAE, which developed as a complication of thoracentesis. Thoracentesis is one of the invasive procedures that can be applied for diagnostic/therapeutic purposes in the ED and does not have complications such as pneumothorax, hemothorax, soft tissue infection, or intra-abdominal organ injury. Physicians should be aware that CAE may also occur in patients who develop neurological deficits after thoracentesis. The clinician’s high suspicion, prompt diagnosis, and treatment can be lifesaving.